POLITIK HUKUM DAN DINAMIKA PERUBAHAN SOSIAL DALAM MASYARAKAT - Muhaimin, M. Sigit (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This paper explores the relationship between legal politics and social change in society. Legal politics refers to the interplay of political power in shaping laws, regulations, and policies that influence societal structure and behavior. As societal dynamics evolve, legal frameworks are often modified or reformed in response to emerging social needs, shifting public opinion, and the growing recognition of human rights. Social change, on the other hand, arises from a range of factors, including technological advancements, economic shifts, and cultural transformations. The paper argues that legal reforms play a critical role in fostering positive social change, while highlighting the challenges involved in ensuring justice and equality. Furthermore, it examines how legal and political systems impact the pace and nature of these social transitions. By analyzing case studies and current practices, this study offers insights into the intricate connection between law, politics, and the evolving social landscape.